Determination of resonance frequency of the respiratory system in respiratory distress syndrome. Issue 3 (1st May 1999) - Lee, S; Alexander, J; Blowes, R; Ingram, D; Milner, A D
Abstract : AIM: To measure tidal volume delivery produced by high frequency oscillation (HFO) at a range of frequencies including the resonance frequency. METHODS: Eighteen infants with respiratory distress syndrome were recruited (median gestation 28.7 weeks). Each was ventilated at frequencies between 8 and 30 Hertz. Phase analysis was performed at various points of the respiratory cycle. HFO was provided by a variable speed piston device. Resonance frequency was determined from the phase relation between the cyclical movements of the piston and pressure changes at the airway opening. Tidal volume was measured using a jacket plethysmograph. RESULTS: The results were most reproducible when analysis was performed at the end of inspiration (within 1 Hz in nine out of 10 cases). Comparison between tidal volume delivery at 10 Hz and resonance frequency was made in 10 subjects. Delivery was significantly higher at resonance than at 10 Hertz (mean percentage increase 92%, range 9–222%). CONCLUSIONS: These preliminary findings suggest that there is improved volume delivery at resonance frequency.